2001
DOI: 10.5194/aab-44-489-2001
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of reproduetive traits in Asturiana de los Valles beef cattle breed

Abstract: SummaryHeritability was estimated for four reproduetive traits in the Asturiana de los Valles breed in order to evaluate the possibility of include this information in the breed's current improvement program. The estimations were done using an animal model except for calving ease score. For this last trait, a threshold model under a sire model was fitted, with the sire effect as the only random effect in the model besides the residual. Estimated heritabilities for calving interval age at first calving, gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
4
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
7
20
4
1
Order By: Relevance
“…Also, the estimate of heritability reported here for CSd (0.226) is approximately 2-fold those of 0.106 and 0.142 reported previously in the breed (Goyache et al, 2003) and also greater than recent estimates reported in multibreed beef cattle populations (from 0.049 to 0.190; Guerra et al, 2006), Brahman cattle (0.06, Riley et al, 2004), and Danish Holsteins for stillbirth (0.10; Hansen et al, 2004). Moreover, heritability estimated here for GLd (0.331) is roughly 3-fold greater than the values of 0.115 (Goyache et al, 2005) and 0.15 (Goyache and Gutiérrez, 2001) previously reported for the Asturiana de los Valles breed considering GL as a dam trait, and twice the estimates recently reported for Canadian Charolais, which ranged from 0.61 to 0.64 (Crews, 2006). Given that these papers analyzed GL as a trait of the dam, the values obtained cannot be directly compared with the current estimates for this trait.…”
Section: Genetic Parameters Within Traitscontrasting
confidence: 38%
See 2 more Smart Citations
“…Also, the estimate of heritability reported here for CSd (0.226) is approximately 2-fold those of 0.106 and 0.142 reported previously in the breed (Goyache et al, 2003) and also greater than recent estimates reported in multibreed beef cattle populations (from 0.049 to 0.190; Guerra et al, 2006), Brahman cattle (0.06, Riley et al, 2004), and Danish Holsteins for stillbirth (0.10; Hansen et al, 2004). Moreover, heritability estimated here for GLd (0.331) is roughly 3-fold greater than the values of 0.115 (Goyache et al, 2005) and 0.15 (Goyache and Gutiérrez, 2001) previously reported for the Asturiana de los Valles breed considering GL as a dam trait, and twice the estimates recently reported for Canadian Charolais, which ranged from 0.61 to 0.64 (Crews, 2006). Given that these papers analyzed GL as a trait of the dam, the values obtained cannot be directly compared with the current estimates for this trait.…”
Section: Genetic Parameters Within Traitscontrasting
confidence: 38%
“…Gestation length was computed as the interval, in days, from the last mating date (one-third of them AI) to calving. Following previous studies, only GL records ranging from 269 to 305 d were included and used for further analyses (Goyache and Gutiérrez, 2001;Goyache et al, 2005). Calf losses were recorded in the CORECA database with the following scores: 1 (calf alive at weaning), 2 (calf sold before weaning), 3 (calf alive at 72 h but dead before weaning), 4 (calf alive at birth but dead within 72 h), and 5 (calf dead at birth).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Regional Government of Principado de Asturias, through the Asturiana de los Valles Breeders Association (ASEAVA), have implemented performance recording (CORECA database) based on nuclei grouping farms according to their proximity and their production system arising from small farm size (GOYACHE and GUTIERREZ, 2001;GOYACHE et al, 2002). We analysed 3,829 single calving records including weaning and birth weights and dates, sex of calf, calving number of the dam and degree of muscularity of dam and calf.…”
Section: Methodsmentioning
confidence: 99%
“…Brief descriptions of the management systems and environmental conditions can be found elsewhere (Goyache and Gutiérrez, 2001;Gutiérrez and Goyache, 2002;Gutiérrez et al, 2007).…”
Section: Methodsmentioning
confidence: 99%